Facile in situ formation of a ternary 3D ZnIn2S4–MoS2 microsphere/1D CdS nanorod heterostructure for high-efficiency visible-light photocatalytic H2 production. Issue 25 (23rd June 2020) - Wang, Lan; Zhou, Hanghang; Zhang, Hongzhong; Song, Yali; Zhang, Huan; Luo, Lingkun; Yang, Yifan; Bai, Shiqi; Wang, Yue; Liu, Shuaixia
Abstract : A novel ternary 3D ZnIn2 S4 –MoS2 microsphere/1D CdS nanorod (ZIS/MoS2 /CdS) photocatalyst was created to achieve excellent photocatalytic H2 evolution under visible light irradiation. Abstract : To achieve high photocatalytic efficiency, developing heterostructure photocatalysts by integrating two or more semiconductor materials into a well-oriented nanostructure is an effective strategy. Therefore, under visible light irradiation, a novel ternary 3D ZnIn2 S4 –MoS2 microsphere/1D CdS nanorod (ZIS/MoS2 /CdS) photocatalyst with excellent H2 evolution ability was prepared. For this purpose, using the solvothermal method, interfacial contact ZIS/MoS2 microspheres were prepared, and 1D CdS nanorods were closely inserted into the interspace of flower-shaped ZIS/MoS2 microspheres, to generate close contact between ZnIn2 S4, MoS2, and CdS. To expedite the production, separation, and transfer of photoinduced electron–hole pairs, this unique ternary heterostructure demonstrated excellent energy level distribution and a dimensional structure. Under the same conditions, the H2 production rate of the component proportion of the 150%-ZIS/10%-MoS2 /CdS (150 wt% ZIS and 10 wt% MoS2 ) photocatalyst reached 7570.4 μmol g −1 h −1, which was ∼39.8 and 69.0 times higher than that achieved using bare ZnIn2 S4 and CdS, respectively. Furthermore, the apparent quantum efficiency (AQE) reached 30.38% at 420 nm within 6 h; thus, for designing photocatalysts with a diversiform structure and spatial charge separation, this study provides new tactics.